1960
DOI: 10.1111/j.1365-2621.1960.tb00319.x
|View full text |Cite
|
Sign up to set email alerts
|

SOME EFFECTS OF SUGARS ON THE BREAKDOWN OF PELARGONIDIN‐3‐GLUCOSIDE IN MODEL SYSTEMS AT 90° Ca,b

Abstract: It has been demonstrated that the three most important factors which determine the rate of breakdown of pelargonidin-3-glucoside, the major anthocyanin of strawberries, are pH, temperature and the presence of oxygen (6,9). Ascorbic acid has a marked effect and sugars also contribute to the breakdown of this pigment (9).Since sugars are present at such high concentration in many strawberry products and since there is a variety of sugars available for use in the preparation of these products, it was considered a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

1965
1965
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…The precipitation of the new colorants appeared more important in this medium. These results were in agreement with data (Tinsley and Bockian, 1960) which reported an increase in anthocyanin degradation rate at higher pH values. Precipitation of anthocyanins and related compounds with an increase of pH has been reported by Shi et al (1992).…”
Section: Anthocyanin and Anthocyanin-derived Pigment Solutions At Phsupporting
confidence: 95%
“…The precipitation of the new colorants appeared more important in this medium. These results were in agreement with data (Tinsley and Bockian, 1960) which reported an increase in anthocyanin degradation rate at higher pH values. Precipitation of anthocyanins and related compounds with an increase of pH has been reported by Shi et al (1992).…”
Section: Anthocyanin and Anthocyanin-derived Pigment Solutions At Phsupporting
confidence: 95%
“…Degradation of anthocyanins from black carrot, elderberry and strawberry followed a first order reaction kinetics as evaluated by the pH-differential method, which is in accordance with previous studies on thermal anthocyanin degradation (Tinsley & Bockian, 1960). Black carrot juices exhibited the highest half-life values of total anthocyanins followed by elderberry and strawberry (Table 3).…”
Section: Effects Of Sugar and Ascorbic Acid On The Half-life Of Totalsupporting
confidence: 80%
“…Elevated HMF levels may affect anthocyanin stability (Tinsley & Bockian, 1960), however, concentrations below 100 mg/L were shown to exert only moderate effects on anthocyanin degradation Table 3 Spectrophotometric evaluation of browning index, BI (%) after 2 or 4 h of heating at 95°C, respectively, and total anthocyanin half-life, T 1/2 (h) of black carrot, elderberry and strawberry juices with and without supplementation of sugars and ascorbic acid [mean ± SD, n = 4].…”
Section: Hmf Formation and Sample Browningmentioning
confidence: 99%
“…The effect of increasing concentration of sirup resulting in lowering the amount of recoverable pigments substantiates the research by Tinsley and Bockian ( 1960), who showed that, in model systems, an increase in the concentration of sugar lowered the amount of extractable anthocyanins in strawberries. The loss of the pigment was noted to be partially dependent upon the formation of degradation products.…”
Section: Ban11mentioning
confidence: 99%